Potensi Ekstrak Daun Pepaya sebagai Inhibitor Korosi dalam Media Asam Klorida pada Baja ST37 - Kemala Putri , Dwi; Akbar, Addin (Politeknik ATI Padang, 2021)
Corrosion is a decrease in the quality of a metal material caused by a reaction with the environment. Reducing the corrosion rate on steel can be done by adding an inhibitor. Papaya leaf extract (Carica papaya.L) can be used as a corrosion inhibitor by immersion method. The effect of inhibitor on corrosion rate had been studied using weight loss method, potentiodynamic polarization method, and observation of steel surface using photooptic. It was found that corrosion rate decrease with increase concentration of papaya leaves extract. The highest inhibiton efficiency is 87.8% in 0.2 M hydrochloric acid with 2% concentration of papaya leaves extract. Potentiodynamic polarization method showed that papaya leaves extract decrease corrotion current. Inhibiton efficiency reached 81.58% in 2% extract concentration in which corrosion current decrease from 0.0266 mA/cm2 to 0.0049 mA/cm2. Analysis of photooptic showed that there is difference on steel surface corroded in hydrochloric acid with inhibitor and without it.